2007
DOI: 10.1177/014860710703100112
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of Ω‐3 Fatty Acids in Parenteral Nutrition Beneficially Alters Phospholipid Fatty Acid Pattern

Abstract: Omega-3-fatty-acids-supplemented fat emulsions for parenteral administration are safe and very well tolerated. This study demonstrates that parenteral administration of omega-3-PUFA-enriched fat emulsions leads to increased incorporation of EPA and DHA into phospholipids in serum and erythrocytes, whereas AA levels remain unchanged. Thus, postoperative parenteral administration of omega-3-PUFA-enriched lipid emulsions could have an impact on the postoperative inflammatory response after abdominal surgery and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
0
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 31 publications
5
58
0
5
Order By: Relevance
“…The present study also showed that ERa and ERb were present in both nuclear and cytosolic compartments, but, in skeletal muscle, localization was preferential to the cytosol, which includes the cellular membrane. Therefore, the effect of n-3 PUFAs on ERs could be indirect, because n-3 PUFA can incorporate into the cell membrane and affect membrane fluidity and permeability (Senkal et al 2007;Armstrong et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The present study also showed that ERa and ERb were present in both nuclear and cytosolic compartments, but, in skeletal muscle, localization was preferential to the cytosol, which includes the cellular membrane. Therefore, the effect of n-3 PUFAs on ERs could be indirect, because n-3 PUFA can incorporate into the cell membrane and affect membrane fluidity and permeability (Senkal et al 2007;Armstrong et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Among 17 studies, 11 studies [2,11,12,23,24,26,27,29,30,32,33] used an adequate approach to sequence generation using computer generated random numbers or random-number tables. The adequacy of randomization was unclear in the remaining 6 studies.…”
Section: Methodological Qualitymentioning
confidence: 99%
“…Figure 1 shows the process for identifying potentially eligible studies and exclusion criteria. After elaborative screening, 34 articles were assessed by full text and 17 studies with 753 patients [2,[10][11][12]15,16,[23][24][25][26][27][28][29][30][31][32][33] were included for the review. However, three publications [2,24,30,31,33] are same study that reported different outcomes.…”
Section: Selection and Characteristics Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations